2019
DOI: 10.1093/tas/txz177
|View full text |Cite
|
Sign up to set email alerts
|

Lamb performance in hardwood silvopastures, II: animal behavior in summer1

Abstract: Integrating trees into pastures, a practice known as silvopasture, may benefit livestock in the summertime through the provision of shade. The purpose of this project was to compare the behavioral patterns of sheep grazing in silvopastures and open pastures. Black walnut (Juglans nigra L.) and honeylocust (Gleditisia triacanothose L.) based silvopasture systems were compared with open pastures in a randomized complete block design with three blocks over two summers. Behavior measures were recorded within a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In the current study, the lambs in solar pastures spent their ruminating and idling activities predominantly under shade (<96%), while 45% of their grazing activity took place in shade directly under the solar panels. Similarly, in a recent silvopastoral study, Pent et al (2020) noted that lambs spent over 90% of daylight hours within the boundaries of the shade. Cloete et al (2000) recorded that lambs born in shaded paddocks were 3.8% heavier at weaning than those were born and raised in paddocks without shade.…”
Section: Lambs Spent Their Time Predominantly Under Shade and Had Similar Or Lower Water Intake Than Those Grazing Open Pasturesmentioning
confidence: 76%
“…In the current study, the lambs in solar pastures spent their ruminating and idling activities predominantly under shade (<96%), while 45% of their grazing activity took place in shade directly under the solar panels. Similarly, in a recent silvopastoral study, Pent et al (2020) noted that lambs spent over 90% of daylight hours within the boundaries of the shade. Cloete et al (2000) recorded that lambs born in shaded paddocks were 3.8% heavier at weaning than those were born and raised in paddocks without shade.…”
Section: Lambs Spent Their Time Predominantly Under Shade and Had Similar Or Lower Water Intake Than Those Grazing Open Pasturesmentioning
confidence: 76%
“…However, sheep experiencing a high radiant heat load when fully exposed to the sun will narrow their prescriptive zone, particularly the superior limit [41]. According to Pent et al [19], a sensitive change by conduction will only be effective if the surface temperature is lower than the body temperature of lambs. The authors also stated that the SP promotes a more effective loss of heat by conduction than open pastures.…”
Section: Thermal Environmentmentioning
confidence: 99%
“…Although animals in the extensive system performed grazing activity more than half of the time and at different times of the day [47], lambs needs to have a thermal environment that stimulates it to seek food. Pent et al [19] evaluated the behavioural repertoire of lambs in a SP system with black walnut (Juglans nigra L.) and honeylocust (Gleditisia triacanothose L.) in the USA and concluded that lambs in the shaded system spent more time grazing. The same authors stated that the activity is performed depending on the comfort conditions when food is not limited.…”
Section: Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Silvopasture is an agroforestry practice defined as the intentional integration and co-management of trees, forages, and livestock (Orefice and Carroll 2017). Benefits include shade for animals, reduced wind speed, nutritious forages, timber and non-timber tree products, and ecosystem services such as increased biodiversity and carbon sequestration (Kurtz 2000;Workman et al 2003;Montagnini and Nair 2004;Buergler et al 2005;Moorhead and Dickens 2012;Pent et al 2020a). There are two general silvopasture establishment methods.…”
Section: Introductionmentioning
confidence: 99%